Pembinaan Prestasi Bola Voli Pasir pada Pusat Pendidikan dan Latihan Pelajar Daerah (PPLPD) Kabupaten Kendal Tahun 2021 - Sabila, Mulya Diva Cahaya; Soenyoto, Tommy (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study is to ascertain how PPLPD sand volleyball athletes in Kendal Regency will be developing their performance in 2021. The research method used is quantitative research with a descriptive analysis approach. The instrument used is an instrument of observation using questionnaires, interviews, and documentation. The data analysis used in this research is descriptive statistical analysis. From the questionnaires that have been carried out, the total results of the overall score of the questionnaire for coaching the achievements of PPLPD Sand Volleyball athletes in Kendal Regency in 2021 consist of 2 respondents in the very good category with a distribution of 10%, 8 respondents in the good category with a distribution of 40%, 5 respondents in the medium category with a distribution of 25 %, 5 respondents in the category of less distribution of 25% and 0 respondents in the category of very less distribution of 0%. So it can be said that the development of the PPLPD Sand Volleyball athlete achievements in Kendal Regency in 2021 mostly said it was in the good category, and no one said it was very lacking. Based on the results of the study, it can be concluded that the development of sports achievement for PPLPD Sand Volleyball athletes in Kendal Regency in 2021 has been carried out well. Suggestions for research are: So that staff and coaches can monitor the progress of athletes directly on the field, because as we know that communication plays an important role in a team